El rey en el destierro: héroes y villanos en Memoirs of Ferdinand VII. King of the Spains - David Loyola López (Cuadernos de Ilustración y Romanticismo, 2020)
During the Spanish liberal exile of 1823, a book titled Memoirs of Ferdinand VII. King of the Spains (1824) was published in London. This book, which was translated by Michael J. Quin from an original text in Spanish and whose author remained in anonymity, reproduces some of the recent events of the Spanish history and the importance that Ferdinand VII had on it. Our principal aim is to analyse the image that the author shows of El Deseado, and the several characters that took part in the story in order to study the objectives that the book pursues in the English —and Spanish— societies of the 19th Century. In conclusion, we expect to describe the heroes and the villains of the Spanish history in the begging of the 19th Century based on the Memoirs of Ferdinand VII. King of the Spains.